PRINCIPLES REGARDING STATE JURISDICTION IN INTERNATIONAL LAW - Oana – Adriana IACOB (Challenges of the Knowledge Society)
The concept of state jurisdiction in international law is based on the principle of sovereign equality, establishing that each state enjoys the exclusive right to exercise authority (with the obligation of non-interference for other members of the international community) over a given territory, its population and its goods, as well as over events and acts committed within its territorial boundaries. The central focus of the present paper is jurisdiction, regarded as a manifestation of sovereignty, referring to the state competence to legislate and apply law to particular events, persons and property. Traditionaly, jurisdiction has been tightly connected to the concept of territory. However, of particular interest is what happens in situations that involve elements of extraneity, when several states claim jurisdiction over a certain event. In this sense, the five principles governing the exercise of state jurisdiction in criminal law matters will be analysed.